Evaluation of carboxylic acid-derivatized corroles as novel gram-positive antibacterial agents under non-photodynamic inactivation conditions. (15th February 2023) - Sautour, Marc; Pacquelet, Sandrine; Gros, Claude P.; Desbois, Nicolas
Graphical abstract: Highlights: New corroles with carboxylic acid functions had been synthesized and characterized. The antiviral activity against two strains of S. aureus is evaluated under non-photodynamic inactivation. The minimum inhibition concentration value of the best one was only 0.78 μg/mL on one of the most common antibiotic-resistant bacterial pathogens. Abstract: Herein, we report the synthesis and evaluation of carboxylic acid corroles bearing either one, two, three of four carboxylic groups as gram-positive antibacterial agents against two strains of S. aureus, one methicillin-sensible (MSSA) and the other methicillin-resistant (MRSA). Lead compounds 5 and 6 show low minimum inhibitory concentrations (MICs) of 0.78 μg/mL against both MSSA and MRSA. These molecules, previously underexplored as antibacterial agents, can now serve as a new scaffold for antimicrobial development.